Less invasive surfactant administration versus intubation-surfactant-extubation in preterm infants: a retrospective study - Gianluca Dini; Maria Grazia Santini; Federica Celi; Alberto Verrotti (Medicinski glasnik, 2024)
Aim: To compare the need for intubation and mechanical ventilation after surfactant delivery between less invasive surfactant administration (LISA)-treated and intuba-tion-surfactant-extubation (IN-SURE)-treated premature infants with respiratory distress syndrome (RDS). Methods: Retrospective registry-based cohort study enrolled 36 newborns admitted to the Neo-natal Intensive Care Unit of the “Santa Maria” Hospital of Terni between 2016 and 2023. As a primary outcome, the need for intubation and mechanical ventilation within 72 hours of life was followed, and major neonatal morbidities and death before discharge as the secondary outcome. Results: The LISA group and the IN-SURE group included 13 and 23 newborns, respectively. Demographic features showed no significant differences between the two groups. The need for mechanical ventilation in the first 72 hours of life was similar in both groups (p>0.99). There were no significant differences in morbidities. Conclusion: LISA and INSURE are equally effective modalities for surfactant administration for the treatment of RDS in preterm infants.
Keywords: newborn; respirato-ry distress syn-drome; surfactant